Proceedings of the Ocean Drilling Program 1989
DOI: 10.2973/odp.proc.sr.104.164.1989
|View full text |Cite
|
Sign up to set email alerts
|

The Stratigraphy of Neogene Silicoflagellates from the Norwegian Sea, ODP Leg 104

Abstract: A quantative study was made of silicoflagellates recovered from Sites 642 (lower Miocene-upper Pliocene), 643 (lower Miocene-upper Miocene), and 644 (upper Pliocene-Quaternary) on the Vdring Plateau. Although disconformities are present in these sequences, they represent a much more complete record of the Neogene than was recovered pre viously in the Norwegian Sea by DSDP Leg 38.Silicoflagellates are rare or absent for glacial sequences younger than 2.65 Ma, and generally sparse and poorly pre served in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A general continued cooling trend eventually reaches the threshold of freezing, setting in motion the powerful positive albedo feedback from snow and ice. Already thirty years ago, Opdyke et al (1966) suggested that "southern-hemisphere glaciation was initiated about 2.5 million years ago", that is, they noticed a strong increase in ice-rafted debris in their piston cores, shortly after 3 Ma (for details, see Barker, Kennett, et al 1990;Bleil and Thiede 1990;Ciesielski, Kristoffersen, et al 1991 ). Thus, we should expect oscillations when the treshold of freezing is just exceeded, as observed.…”
Section: The Third Great Cooling Step: the Northern Hemisphere Entersmentioning
confidence: 99%
“…A general continued cooling trend eventually reaches the threshold of freezing, setting in motion the powerful positive albedo feedback from snow and ice. Already thirty years ago, Opdyke et al (1966) suggested that "southern-hemisphere glaciation was initiated about 2.5 million years ago", that is, they noticed a strong increase in ice-rafted debris in their piston cores, shortly after 3 Ma (for details, see Barker, Kennett, et al 1990;Bleil and Thiede 1990;Ciesielski, Kristoffersen, et al 1991 ). Thus, we should expect oscillations when the treshold of freezing is just exceeded, as observed.…”
Section: The Third Great Cooling Step: the Northern Hemisphere Entersmentioning
confidence: 99%
“…Scientific drilling was conducted adjacent to transform margins during DSDP Leg 36 (Barker, Dalziel et al, 1976) and ODP Leg 114 (Ciesielski, Kristofferson, et al, 1988) in the Falkland area and ODP Leg 122 in the Exmouth Plateau (Haq, von Rad, O'Connell, et al, 1990).…”
Section: Introductionmentioning
confidence: 99%